PENGARUH MEDIA PUZZLE AKSARA JAWA TERHADAP KEMAMPUAN MENULIS AKSARA JAWA - Bamas Aprihadi Setiawan (Universitas Muhammadiyah Purwokerto, 2018)
Javanese letter is an original Indonesian culture heritage. As a part its conservation, on 2 October 2009, UNICODE, as an institution under UNESCO, determined that Javanese letter was equally admitted what the other letter over the world such as Latin, Chinese, Arabic, and Japanese. However, this condition was not balanced with the development of the Javanese letter in Indonesia, especially by the Javanese people. This research was aimed at revealing more effect of the puzzle media of Javanese letter toward the student competence in writing Javanese Letter in class III-A as the control class and class III B as the experiment class. All the student of class III are homogeny, therefore the sampling technique used Simple Random Sampling. The data collection in this research was by test results. The data was calculated by normal, homogeny test and t-test. The result of student and was accepted therefore the puzzled media after better toward the students' competence in writing and reading Javanese Letter.